Efficacy of an internal anchoring plastic stent to prevent migration of a fully covered metal stent in malignant distal biliary strictures: a randomized controlled study - Paik, Woo Hyun; Woo, Sang Myung; Chun, Jung Won; Song, Byeong Jun; Lee, Woo Jin; Ahn, Dong-Won; Lee, Yoon Suk; Choi, Young Hoon; Ryu, Ji Kon; Kim, Yong-Tae; Lee, Sang Hyub (Endoscopy, 2020)
Background Two types of self-expandable metal stents (SEMS) are available for malignant distal biliary obstruction: fully covered SEMS (FCSEMS) and uncovered SEMS. FCSEMS can prevent stent ingrowth, but a major concern is spontaneous migration. This study aimed to determine whether the additional insertion of a double-pigtail plastic stent to anchor the FCSEMS can prevent migration.Methods 68 patients with unresectable, malignant, distal, biliary obstruction were included in this multicenter, randomized, superiority trial. The patients were randomly assigned to receive either the FCSEMS plus an anchoring plastic stent (n = 33) or an FCSEMS alone (n = 35). After placement of the FCSEMS, the anchoring stent was inserted inside the FCSEMS. The primary outcome was the rate of stent migration during the 6-month follow-up. The secondary outcomes were stent-related adverse events, stent patency, and survival rates.Results The baseline characteristics were similar between the two groups. The rate of stent migration at 6 months was significantly lower in patients with the FCSEMS plus anchoring stent (15 % vs. 40 %; P = 0.02). The mean stent patency was significantly longer in the FCSEMS plus anchoring group (237 days [95 % confidence interval [CI] 199 to 275] vs. 173 days [95 %CI 130 to 217]; P = 0.048). There were no significant differences in stent-related adverse events and overall survival rates at 6 months between the two groups.Conclusions Our data suggest that the additional double-pigtail plastic stent anchored the FCSEMS to prevent migration and prolonged patency without any serious adverse events.